Women making meaning of their desistance from offending: an interpretative phenomenological analysis - GOMM, REBECCA,MARIA (2016)
It is recognised that women who have offended comprise a vulnerable group having commonly experienced trauma and abuse. However, the dominant risk paradigm and assessment tools used within the Criminal Justice System have excluded women offenders in the research base. Similarly, current approaches to desistance, which is concerned with the cessation of offending, have neglected the perspective of women offenders. This study explores an alternative approach, based upon women offenders perspectives, to inform upon intervention and support which encourages desistance from offending. Resilience theory provides a broad framework for the study, in which in depth interviews were conducted with a purposeful sample of 15 ethnically diverse women drawn from probation services and third sector agencies. Documentary records which included offence history and Probation assessment records were utilised to provide a rich context to the research. Interpretative phenomenological analysis was used to explore the women’s experiences and understandings of their offending behaviour, as well as how they found meaning in the support and interventions received from these services. Findings revealed complex histories of childhood neglect and abuse, interpersonal violence in adult relationships, including rape and mental health needs. Of particular importance was the value placed by the women on interventions and approaches that focussed on enabling them to build resilience, through relational resources and self-efficacy beliefs. Barriers to building resilience were related to adaptive behaviours, including the understanding that trust in relationships was paradoxical. Another barrier was posed through lack of self-efficacy beliefs. The study concludes that desistance from offending is underpinned by the process of building resilience for recovery in women offenders. It is recommended that building resilience to support the recovery journey is translated into policy and practice and that the way in which women offenders are assessed based on risk to the public is reconceptualised to inform this